Distribution and Stability of Quinone Outside Inhibitor Fungicide Resistance in Populations of Potato Pathogenic Alternaria spp. in Wisconsin - Ding, Shunping (Plant disease, 2019)
Quinone outside inhibitor (QoI) fungicides have been an important class in managing potato early blight caused by Alternaria solani and brown spot caused by A. alternata. Because of the single-site mode of action character of QoI fungicides, which are relied on for management of diseases in Wisconsin, and the abundant asexual conidia production of the Alternaria species, pathogen isolates with QoI resistance have been detected after just a few years of QoI fungicide usage in commercial production fields. Resistance to QoIs has been attributed to amino acid substitutions F129L and G143A in cytochrome b of A. solani and A. alternata, respectively, as a result of point mutations. The aim of this study was to assess Alternaria populations in Wisconsin for QoI resistance before and after fungicide applications in order to evaluate resistance stability. A TaqMan single nucleotide polymorphism genotyping assay was designed based on the sequences of the cytochrome b gene from Alternaria isolates collected in Wisconsin to profile QoI resistance in Alternaria populations as well as to explore factors that may influence frequency of QoI resistance in the pathogen populations. This assay successfully identified the mutations conferring QoI resistance in isolates collected from four locations each year from 2015 to 2017. During the course of this study, the frequency of A. solani isolates with the F129L mutation was consistently high and showed primarily the TTA mutation type. The frequency of A. alternata isolates with the G143A mutation started relatively low and increased at the end of the production season in each year (P = 0.0109, P = 0.2083, and P = 0.0159). A potato field managed without use of QoI fungicides showed a significantly lower (P < 0.05) frequency of A. alternata isolates carrying G143A than conventionally managed potato fields. The overall frequency of A. alternata isolates carrying G143A in the four locations was similar over the 3 years (P = 0.2971). The QoI resistance characteristics of the isolates were stable even when QoI selection pressure was removed for at least five subculture transfers, and the mutation types of codons 129 and 143 in the cytochrome b gene in A. solani and A. alternata, respectively, remained the same. This indicated that the application of QoIs in the field is not the sole factor responsible for the variation of the frequency of QoI resistance in the pathogen populations